A Discourse of Beauty Standards in Japanese Beauty Product Advertisement (Japanese Women Perspective) - Paramita, Ni Made Savitri; Lestari, Eka Marthanty Indah (Future Science / FSH-PH Publications, 2023)
This study uses a Fairclough Critical Discourse Analysis to analyze advertisements' textual and visual elements and discursive and sociocultural analysis of beauty product advertisements in Japan. Data were taken and studied from several examples of beauty product advertisements and interviews with seven Japanese women as informants about the discourse in beauty product advertisements. In addition, the speakers were also asked to express their opinions regarding the beauty standards in Japanese society today. The results show that advertising has a role in reproducing and maintaining the standard of beauty in Japanese society. The image of women with clean and shining white skin is still the standard for Japanese women. Taglines and beauty products in Japan offer clean white skin as demanded in Japanese society. From this, it is also known that advertising producers use beauty constructions formed in society to make advertisements for beauty products. This causes the discourse on Japanese beauty standards to persist in Japanese society.